Большой хапок: [повести] / Сергей Рокотов - Рокотов Сергей Григорьевич (Русский бестселлер, 2000)
Экземпляры: ф.6 (2003) / Инвентарный номер: 46023 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Р 66 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44